Morphometric and DNA-based identification of horseshoe crab Carcinoscorpius rotundicauda (Latreille, 1802) and Tachypleus gigas (Müller, 1785) from Bangladesh coast (Bioresearch Communications, 2024)
Horseshoe crabs are the living fossils of xiphosurans that have survived for over 200 million years without morphological change and records fossil dating back 500 million years. A study was conducted on morphometric and molecular characterization of horseshoe crab Carcinoscorpius rotundicauda (Latreille, 1802) and Tachypleus gigas (Müller, 1785) from Bangladesh waters. A total of ten samples of C. rotundicauda and one sample of T. gigas were collected from Dublar Char, Sundarbans and Cox’s bazar from June 2016 to May 2017 and February 2024, respectively. Among them, four specimens were male and seven female. Morphometric measurements were taken from all the collected samples and differentiated male and female based on the second pair of legs, the pedipalps. The species were genetically identified using mitochondrial cytochrome c oxidase subunit I (COI) gene. An average length of about 670.5 bp nucleotide sequences were obtained. Average percentage of nucleotide frequencies were T (30.3), C (16.3), A (34.4) and G (19.0) for C. rotundicauda and T (34.45), C (22.01), A (27.91) and C (15.63) for T. gigas. GC content analysis showed that average GC 36.20% and AT 63.80%. The average GC content at the 1st, 2nd and 3rd codon position were 38.82%, 37.87% and 31.92% respectively.  This is the first report of DNA barcoding of a living fossil C. rotundicauda and T. gigas from Bangladesh and will serve as baseline information for future research, conservation and management of this invaluable primitive creature.Bioresearch Commu. 10(2): 1489-1494, 2024 (July)